The Mediation Effect of Moral Disengagement on Spiritual-Religious Attitudes and Academic Dishonesty among Guidance and Counseling Students: Array - Endang Rifani; Sugiyo Sugiyo; Edy Purwanto (Islamic Guidance and Counseling Journal, 2021)
Academic dishonesty is a morality problem that is often found in every level of education. It becomes a concern among guidance and counseling practitioner in the educational context. Regarding previous studies, spiritual-religious attitudes and moral disengagement predict individuals’ academic dishonesty. To complete the gap of those studies, the current study investigated the role of moral disengagement to mediate the relationship between spiritual-religious attitudes and academic dishonesty in university students. There were 292 respondents from four universities in Semarang participated in this study. The authors used a cross-sectional study and utilized google form to collect the data. The authors conducted three analyses, regression-based path analysis, mediation analysis using bias-corrected and bootstrapping. The results showed that there was a direct relationship among all variables, but they're found no mediation effect on moral disengagement. These findings imply the importance of counseling services to preserve students’ morality so they could avoid academic dishonesty.